2021
DOI: 10.1016/j.cegh.2021.100862
|View full text |Cite
|
Sign up to set email alerts
|

Rate of smoking cessation and factors associated with successful quit smoking in Seremban District of Malaysia

Abstract: Introduction: Smoking is a major public health significant and a leading preventable cause of premature mortality. Assisting smoking cessation is important due to potential positive health impacts. The establishment of "Quit Smoking Clinics" reflect a great commitment by the health authority to reduce the national burden of smoking prevalence. Aim: The objective is to measure the prevalence of smoking cessation and factors associate with successful quit smoking in all public healthcare "Quit Smoking Clinic" in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…For example, in Turkey studies (Saylan et al, 2021) have reported smoking cessation interventions with quit rates between 22% and 51%. In Malaysia (Zamzuri et al, 2021), they developed a structured programme using a private public partnership (mQuit) with success rates of approximately 30%. Through this study, we believe that our results will provide policy makers especially in low-middle income countries on the effectiveness of such programmes and how these can be adapted to suit their context.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…For example, in Turkey studies (Saylan et al, 2021) have reported smoking cessation interventions with quit rates between 22% and 51%. In Malaysia (Zamzuri et al, 2021), they developed a structured programme using a private public partnership (mQuit) with success rates of approximately 30%. Through this study, we believe that our results will provide policy makers especially in low-middle income countries on the effectiveness of such programmes and how these can be adapted to suit their context.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Over recent years, successful quit smoking rates were reported as ranging from 30.2% to 45.5% [7]- [11]. A study in South Korea reported almost 40.0% of smokers accomplished smoking cessation following a 12-week quit smoking intervention [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Karachi, Pakistan, a study among 330 former adult smokers, 50.3% quit successfully on their first attempt [12]. A recent study by Ahmad Zamzuri, Kamarudin [7] among smokers attending "Quit Smoking Clinic" in Seremban district, Malaysia discovered 30.2% had effectively stop smoking after six month of clinic follow-up. Among the ever smokers in Malaysia, at least one third of them have ceased smoking behaviour [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations